Perlindungan Hukum Terhadap Whistleblower Dalam Perkara Tindak Pidana Korupsi Oleh Pemerintah Kota Pangkalpinang - Riko Aji Pratama; Muhamad Hasan Sebyar (Aliansi: Jurnal Hukum, Pendidikan dan Sosial Humaniora, 2024)
The difficulty of eradicating corruption today has become a challenge for law enforcement officials. The vital role of a whistleblower (reporting witness) as a witness to reveal the facts in cases of criminal acts of corruption is very necessary. Therefore, the government must provide legal protection guarantees to whistleblowers (reporting witnesses) who provide information about suspected indications of corruption. This scientific research aims to find out what steps to protect whistleblowers are provided by the Pangkalpinang City Government. This scientific study applies empirical legal research methods, by conducting a study of legal protection for whistleblowers in cases of criminal acts of corruption by the Pangkalpinang City Government. Meanwhile, the research approaches applied are the conceptual approach and the statute approach. The results of the study show that the Pangkalpinang City Government guarantees protection for whistleblowers in cases of criminal acts of corruption, this can be seen from the issuance of Mayor Regulation Number 31 of 2016 concerning General Guidelines for the Complaint Handling System (whistleblower system) for Corruption Crimes within the Pangkalpinang City Government.